Microcytosis as a risk marker of cancer in primary care: a cohort study using electronic patient records - Hopkins, Rhian (Br J Gen Pract, 2020)
BACKGROUND: Microcytosis (smaller than normal red blood cells) has previously been identified as a possible early risk marker for some cancers. However, the role of microcytosis across all cancers has not been fully investigated. AIM: To examine cancer incidence in a cohort of patients with microcytosis, with and without accompanying anaemia. DESIGN AND SETTING: Cohort study of patients aged ≥40 years using UK primary care electronic patient records. METHOD: The 1-year cancer incidence was compared between cohorts of patients with a mean red cell volume of <85 femtolitres (fL) (low) or 85–101 fL (normal). Further analyses examined sex, age group, cancer site, and haemoglobin values. RESULTS: Of 12 289 patients with microcytosis, 497 had a new cancer diagnosis within 1 year (4.0%, 95% confidence interval [CI] = 3.7 to 4.4), compared with 1465 of 73 150 without microcytosis (2.0%, CI = 1.9 to 2.1). In males, 298 out of 4800 with microcytosis were diagnosed with cancer (6.2%, CI = 5.5 to 6.9), compared with 940 out of 34 653 without (2.7%, CI = 2.5 to 2.9). In females with microcytosis, 199 out of 7489 were diagnosed with cancer (2.7%, CI = 2.3 to 3.1), compared with 525 out of 38 497 without (1.4%, CI = 1.3 to 1.5). In patients with microcytosis but normal haemoglobin, 86 out of 2637 males (3.3%, CI = 2.6 to 4.0) and 101 out of 5055 females (2.0%, CI = 1.6 to 2.4) were diagnosed with cancer. CONCLUSION: Microcytosis is a predictor of underlying cancer even if haemoglobin is normal. Although a benign explanation is more likely, clinicians in primary care should consider simple testing for cancer on encountering unexplained microcytosis, particularly in males.